2014
DOI: 10.5296/jas.v2i1.4890
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Choice of Climate Change Adaptation Strategies by Households: A Case of Mpolonjeni Area Development Programme (ADP) in Swaziland

Abstract: The increased involvement of food relief agencies nearly on an annual basis is a clear indication that agricultural production continues to decline as a result of climate change. In order to mitigate the negative effect of climate change, households engage on adaptation strategies. The extent to which these impacts are felt depends mostly on the level of adaptation in response to climate change. The main objectives of the study were to identify the adaptation strategies employed by households and to analyse fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 5 publications
5
33
0
Order By: Relevance
“…They also suggested that the preference of adaptation choice was positively influenced by access to information (e.g., agricultural extension services). Additionally, belief of climate change was reported to pose a significant influence on adaptation behavior [28,40,41]. Ho and Shimada [15] found that the higher the pressures local farmers heard or saw from their neighbors, relatives or friends, the less they adapted their rice farming in response to climate change.…”
Section: Data Descriptionmentioning
confidence: 99%
“…They also suggested that the preference of adaptation choice was positively influenced by access to information (e.g., agricultural extension services). Additionally, belief of climate change was reported to pose a significant influence on adaptation behavior [28,40,41]. Ho and Shimada [15] found that the higher the pressures local farmers heard or saw from their neighbors, relatives or friends, the less they adapted their rice farming in response to climate change.…”
Section: Data Descriptionmentioning
confidence: 99%
“…However, as the major livelihoods of the dry zone people are agriculture, they mostly focused on the agricultural adaptation practices and its related adaptation measures. The acceptance of climate change adaptation strategies is determined by numerous demographic, socioeconomic and organization or institutional characteristics (Deressa et al, 2009;Hassan and Nhemachena, 2008;Yusuf et al, 2008;Shongwe et al, 2014). Adaptation involves harms and opportunities, as well as failures and successes, as the effect of climate occurs over a span of time (WICCI, 2011).…”
Section: Perceptions Of Local People On Adaptation Tomentioning
confidence: 99%
“…Even though human and natural systems have a certain capacity to cope with adverse circumstances, adaptation will be needed to maintain this capacity with continuing climate change (IPCC, 2012). In this regard, the choice of local farmers in climate change adaptation strategies is determined by demographic characteristics, socio-economic characteristics at the household level, organizational or institutional characteristics and by the agroecological contexts (Hassan and Nhemachena, 2008;Yusuf et al, 2008;Deressa et al, 2009;Shongwe et al, 2014;Tessema et al, 2013;Oo et al, 2017). Therefore, in this study, the local participants perceived the adaptation measures at the household level in the context of localized agro-ecological settings as the study was conducted in the dry zone area.…”
Section: Perceptions Of Local People On Adaptation Tomentioning
confidence: 99%
“…In contrast education and sex status of head of household is insignificant to adoption to climate change In Swaziland farmers has adopted varieties resistant to drought, irrigation, switching of crops, crop rotation, early planting, late planting, mulching, intercropping and minimum tillage. These practices are found to be significantly affected by household head's age, membership in social group, category of land, availability of credit, assessment to extension service and training, incidence of pest and disease, high price of inputs and food (Shongwe et al, 2014).…”
Section: Climate Change Impacts On Chepang Communitymentioning
confidence: 99%
“…In the same way adoption in Swaziland is significantly affected by household head's age, membership in social group, category of land, availability of credit, assessment to extension service and training, incidence of pest and disease, high price of inputs and food. In contrast education and sex status of head of household is insignificant to adoption to climate change (Shongwe et al, 2014). Charles and Rashid (2007) identified that assessment to credit and extension and climate change awareness are some of the important determining factor for adaptation at farm level in South Africa, Zambia and Zimbabwe.…”
Section: Factors Affecting Adoption Of Climate Change Adaptation Stramentioning
confidence: 99%